Octopus hug - Pringle, Laurence P.; Palmer, Kate Salley (Honesdale, Pa. : Boyds Mills Press, Inc., 1993)
When Mom goes out for the evening, Dad and the kids invent games filled with fun and laughter, and they all learn how to give an octopus hug.
Book Links (A.L.A.).
Publisher's Weekly.
School Library Journal.
2.5
K-3
Keywords: Family life -- Fiction; Fathers -- Fiction; Family life -- Fiction; Fathers -- Fiction